2012
DOI: 10.3892/etm.2012.696
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of heat shock protein 27 in the susceptibility of KT human breast cancer cells to UVC and interferon lethality

Abstract: Revealing the key molecules regulating the stress-response pathways in human cells is an intriguing problem. Chaperones, such as glucose-regulated protein 78 (GRP78) and heat shock protein 27 (HSP27), are important molecules for protecting the viability of human cells; however, it remains to be further clarified whether the molecules differentially modulate cellular responses to various types of stressors, such as DNA-damaging ultraviolet ray C (principally 254-nm wavelength, UVC) and cytocidal cytokine interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The overexpression of Hsp27 in AS-B145 or BT-474 breast cancer cells diminished the inhibitory effect of ovatodiolide on mammosphere formation [26], while the phosphorylation of Hsp27 at Ser15 promoted its Ser78 phosphorylation and enhanced the nuclear localization of HER2 to induce Trastuzumab (TZMB) resistance in HER2 + breast cancer cells [27]. Hsp27-overexpressing KT breast cancer cells showed increased resistance to ultraviolet ray C (UVC) and interferon lethality [28], and our recent study also found that phosphorylated Hsp27 promoted ADR resistance in MCF-7 and MDA-MB-231 breast cancer cells by regulating DNA damage repair protein c-Myc dual phosphorylation [29]. A proposed model of Hsp27 in breast cancer development is illustrated in Figure 2.…”
Section: Hsp27mentioning
confidence: 99%
“…The overexpression of Hsp27 in AS-B145 or BT-474 breast cancer cells diminished the inhibitory effect of ovatodiolide on mammosphere formation [26], while the phosphorylation of Hsp27 at Ser15 promoted its Ser78 phosphorylation and enhanced the nuclear localization of HER2 to induce Trastuzumab (TZMB) resistance in HER2 + breast cancer cells [27]. Hsp27-overexpressing KT breast cancer cells showed increased resistance to ultraviolet ray C (UVC) and interferon lethality [28], and our recent study also found that phosphorylated Hsp27 promoted ADR resistance in MCF-7 and MDA-MB-231 breast cancer cells by regulating DNA damage repair protein c-Myc dual phosphorylation [29]. A proposed model of Hsp27 in breast cancer development is illustrated in Figure 2.…”
Section: Hsp27mentioning
confidence: 99%